O pensamento autoritário brasileiro e as relações internacionais : a crise do período entre guerras na obra de Francisco Campos - Vizentini, Paulo Gilberto Fagundes (1983)
This Study, based on a multidisciplinary view, analyses the perception which the brazilian authoritarian thought has about the international crisis of the period between wars. Using primarily the instruments of the political sciences analysis, we also search the support of the interpretative categories of History and Ideology.